The Analysis of Open Defecation Behaviour After Implementing the Tringger of Pillar 1 in Society Based Total Sanitation at Tulungagung Regency - Ida Ayu Anom Putrika; Indasah Indasah; Siti Farida Noor Laila (Journal for Quality in Public Health, 2018)
Open defecation behavior is still practiced by some people who have obtained trigger pillar 1 society based total sanitation. The objective of the study is to analyze the factors that influence open defecation behavior after triggering implementation pillar 1 society based total sanitation.The research design used in this research is survey expansion. The population is the head of family with the behavior of open defecation that has obtained trigger pillar 1 in society-based total sanitation at Tulungagung regency. The sample size is 100 respondents by using Cluster sampling technique. Data were collected by using questionnaire, then the data were analyzed by using logistic regression. The results showed that a bad Open Defecation (57%), low economic status (97%), good knowledge (100%), bad culture of defecate (79%), good family support (95%), less community support that is 58 respondents (58%), good community leaders support (100%), distance of house where chapter other than closet (98%). Statistical test results in Overall Statistics with a significance value of (p) 0, 000 which means that there are variables that affect the behavior of OD . When viewed the value (p) on each independent variable is economic status variables have a value (p) of 0, 043; knowledge has value (p) of 1,000; attitude has a value (p) 0.383; cultural variables have value (p) 0,000; family support variables have (p) 0.046; the community support variable has (p) 0.004; support of community leaders have value (p) 0,125 and the distance of trowing feces place another of water closet variable has the value (p) 0, 215. Open defecation behaviour after implementing the tringger of pilar 1 in Society-based total sanitation affected by factor cultur, community support, economic status and family support.